Konsep Pendidikan Akhlak dan Pembentukan Kepribadian dalam Risālah Ibn al-Qayyim ilā Aḥadi Ikhwānihi - Yahya Yahya; Asmaji Asmaji (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This article analyzes the concept of moral education presented in Ibn al-Qayyim’s “Risālah ilā Aḥadi Ikhwānihi,” a concise yet profound work that encapsulates essential principles of spiritual refinement and character formation in Islamic thought. Using a qualitative library research method, this study examines the central educational ideas of the risālah and connects them with contemporary Islamic educational discourse. The findings indicate that Ibn al-Qayyim structures moral education upon four fundamental pillars: patience (ṣabr), certainty (yaqīn), love of God (maḥabbah), and spiritual striving (mujāhadah). These pillars form an integrated framework that strengthens intellectual understanding, emotional stability, and spiritual awareness. The risālah further emphasizes the crucial role of tazkiyah al-nafs (purification of the soul), the unity of knowledge and action, and the transformative power of sincere worship in shaping a Muslim’s character. The study concludes that the educational values articulated in this work offer significant relevance for modern Islamic education, particularly within pesantren, tahfiz institutions, and character-based Islamic learning environments. Keywords: Islamic education; moral education; Ibn al-Qayyim; character formation; tazkiyah al-nafs